INTENSITAS ASET TETAP, LEVEREGE, INVENTORY INTENSITY DAN PENGARUH TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Non-Cyclical Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2023) - Wulandari, Hana Dwi; Choirunissa, Syifa; Ramadhani, Salsa Bila Putri; Rahmaningrum, Lidia; Kurniawan, Dicky Febri (Cahaya Ilmu Bangsa, 2024)
This study aims to examine the effects of the effect of fixed assets, leverege and inventory intensity on tax avoidance. This research is associative quantitives with secondary data used in this study originating from financial statements and company annual reports Non cylical registered on the official website of the Indonesia Stock Exchange and the official website of the non cylical company in 2020-2023. There are 9 company data used as samples obtained through purposive sampling. The analytical method used is multiple linear regression analysis with the help of the EViews 12 program. The results of this study indicate that the intensity of fixed assets, leverege and inventory intensity together influence tax avoidance, the intensity of assets remains influencing tax avoidance, Leverege does not affect tax avoidance, and Inventory Intensity does not affect tax avoidance.